A preventive action management platform in healthcare information systems - Peixoto, Hugo (2015)
Preventive actions management plays a crucial role in clinical applications, not only for those who depend on data to make decisions, but also for those who monitor the operational and financial impact of the systems. This paper presents an open-source platform, named ScheduleIT, capable of managing preventive routines. The platform is based on an estimation model that determines the optimal time interval for interventions, according to the criticality of the system and the number of non-programmed faults, among others. ScheduleIT has a web-based interface available to different area end-users, ranging from IT technicians to administrative staff. At this point, the platform covers around 75% of the healthcare systems and it is full accepted by its main users as a reliable and effective preventive tool.